KEHARUSAN MEMAJUKAN MADRASAH - Ahmad Tanaka (IAI Al-Mawaddah Warrahmah Kolaka, 2018)
In the past few years superior madrasa have emerged. Its superiority is not only at the local level, but also nationally, even some madrassas have recognized international superiority. For example, MI and State MTs in Malang, MI Development in Jakarta, MAN Insan Cendekia in Serpong, and MAN Insan Cendekia in Gorontalo. But the number of superior madrasas is very little compared to the number of madrasas as a whole. The above facts show that to become an advanced school or madrasa it is not enough to rely solely on the excellence of the curriculum in the quantitative sense, namely in the form of a series of subjects. Many factors are very influential, such as management, quality of human resources, funding, management, and so on. Therefore it is very understandable that madrasas, however in terms of curriculum content have advantages compared to schools, cannot yet become advanced educational institutions because they still face various problems. In the map of Indonesia's earth, the existence of madrassas actually has very strong foundations because it is supported by the nation's ideology (Pancasila), the 1945 Constitution, the Law of the National Education System, namely Law No. 20 of 2003 and the law on previous education. Therefore, efforts to build and advance madrasas are valid, even a necessity. In fact, the dynamics of madrasa development put more madrasas as educational institutions that received less attention from the government. As a result the existence of madrasas is faced with quite complex problems. Initially was a problem of recognition, a problem of funds, and then impacting on other problems. For that, there was a need for serious and comprehensive efforts to unravel the problems faced by madrassas and find solutions. Among the solutions offered are using structural, cultural and managerial approaches.